Analysis of Psychological Foundations in the Development of Islamic Cultural History Curriculum - Dwi Ramadhannita, Retno; Mulyawan Safwandy Nugraha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Curriculum is an important part of education and affects all educational activities. The main purpose of the psychological foundation in curriculum development is to provide a better understanding of how curriculum developers see students as subjects of education. Based on the observations that have been made at Modern Riyadhul Jannah Junior High School, teachers feel that student understanding is important in developing the Islamic Cultural History curriculum. The curriculum must be designed in such a way that students can understand the basic concepts in the history of Islamic culture. A curriculum that needs to be simplified or more abstract will help student understanding. Therefore, the use of clear language and structured material will make it easier for students to understand the material being taught. The researcher adopted a qualitative approach within a descriptive research framework. Data collection techniques using observation, interviews, and documentation. The results revealed that Riyadhul Jannah Modern Junior High School teachers have successfully developed a curriculum with detailed learning objectives that pay attention to the situation, conditions and needs of students. The teachers agreed that the management of students' learning experiences must be done well in order to match the set objectives. In this context, it shows that psychological foundations are important to consider when developing the SKI curriculum. This study provides direct examples of how psychological foundations can be applied when creating the SKI curriculum and provides suggestions for future SKI curriculum development.